2009
DOI: 10.1186/1472-6823-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Familial history of diabetes and clinical characteristics in Greek subjects with type 2 diabetes

Abstract: Background: A lot of studies have showed an excess maternal transmission of type 2 diabetes (T2D). The aim, therefore, of the present study was to estimate the prevalence of familial history of T2D in Greek patients, and to evaluate its potential effect on the patient's metabolic control and the presence of diabetic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
20
3
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 37 publications
20
20
3
5
Order By: Relevance
“…In contrast, the Greek study on type 2 DM patients showed a reduced HbA1c level in patients with coexisting hypothyroidism (7.38% compared to 7.81%) although this was statistically insignificant. [9] The same observation was made by Kim et al in Taiwan, with a mean HbA1c of 8.8% and 8.4% in euthyroid and hypothyroid diabetic individuals respectively. [10] The variations in the above observations and the absence of any significant findings is probably due to the multiple mechanisms by which hypothyroidism can decrease as well as increase the blood glucose values.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, the Greek study on type 2 DM patients showed a reduced HbA1c level in patients with coexisting hypothyroidism (7.38% compared to 7.81%) although this was statistically insignificant. [9] The same observation was made by Kim et al in Taiwan, with a mean HbA1c of 8.8% and 8.4% in euthyroid and hypothyroid diabetic individuals respectively. [10] The variations in the above observations and the absence of any significant findings is probably due to the multiple mechanisms by which hypothyroidism can decrease as well as increase the blood glucose values.…”
Section: Discussionsupporting
confidence: 63%
“…Em nosso estudo, apenas 3% das pacientes com DMG não teriam sido investigadas se tivessem sido adotados os critérios de rastreamento seletivo recomendados pela American Diabetes Association (ADA) A história familiar de diabetes tipo 2 é considerada um forte fator de risco para DMG, com relato de aumento de 68% no risco para a doença na presença desse fator (19). Além disso, diversos estudos têm demonstrado uma grande prevalência de diabetes materno em pacientes com diabetes tipo 2 em diferentes populações (20,21). Bo e cols., analisando a prevalência de história Tabela 9.…”
Section: Discussionunclassified
“…For example, absence of excess of maternal transmission was observed in South Indian [10] as well as in Korean population with T2DM [11], supported later by a study on Western Indian population [12]. It was suggested that parental T2DM was an independent risk factor for offspring of T2DM in Korean population Kim et al On the other hand, in recent years presence of excess maternal transmission of T2DM has been documented in Greek diabetics [13], supporting previous studies in Brazil [14], and Norway [15]. A very recent finding by Abbasi et al on population of Netherland showed that both maternal and paternal diabetes seem to be associated with increased risk of T2DM, independently of diet, lifestyle and obesity [16].…”
Section: Introductionmentioning
confidence: 63%
“…McCarthy et al in contrast did not find any difference of transmission of diabetes in their population [27], but in several studies maternal transmission was found in different populations [13,14,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%